Identifying barriers to Academia-Industry relationships in the MPCs, and their impact on Research and Innovation cooperation between the EU and MPCs - Rodriguez Clemente R.; Martinez-Blanch J.; Rossano M.; Zebakh S. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
Collaboration between Academia and Industry at both national and international level is a pivotal issue to strengthen competiveness of countries and face major future challenges. The inputs needed to develop such a kind of cooperation and the main barriers hampering the implementation of joint activities are analyzed in this paper taking into account the results of a survey carried out in the framework of the MIRA project. Finally some suggestions are provided to support the implementation of policies and instruments aimed at enhancing the necessary links and contributing to the establishment of a Euro-Mediterranean Innovation Space.